Pengaruh Media Pembelajaran Komik Digital Klik (Komik Literasi Keuangan) terhadap Hasil Belajar Kognitif pada Mata Pelajaran IPS Siswa Kelas VII SMP Negeri 22 Malang (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the influence of digital comic learning media KLIK (Financial Literacy Comics) on cognitive learning outcomes in social studies subjects of grade VII students of SMP Negeri 22 Malang. The approach used in this study is a quantitative approach. The type of research used is an experimental type of research with a Posttest Only Control Group Design research design. The population in this study is all grade VII students of SMP Negeri 22 Malang with the sample used, namely grade VII B students as the experimental class and grade VII G as the control class. The instrument used to measure students' cognitive learning outcomes is test questions. The data analysis techniques used in this study were data instrument tests with validity tests and reliability tests, prerequisite tests with normality tests and homogeneity tests, and hypothesis tests using t-tests. The results of the study showed that there was a partial influence of digital comic learning media KLIK (Financial Literacy Comics) on students' cognitive learning outcomes. This is evidenced by the results of data analysis with the help of SPSS 22 for Windows which shows 0.000 < 0.05 which means that H0 is rejected and H1 is accepted.